Are low interest rates firing back? Interest rate risk in the banking book and bank lending in a rising interest rate environment - Lara Coulier; Cosimo Pancaro; Alessio Reghezza (European Central Bank (ECB), 2024)
We match granular supervisory and credit register data to assess the implications of banks' exposure to interest rate risk on the monetary policy transmission to bank lending supply in the euro area. We exploit the largest and swiftest increase in interest rates since the creation of the euro and find that banks with a higher exposure to interest rate risk, i.e., with a larger duration gap after accounting for hedging, curtailed corporate lending more than their peers. Ceteris paribus, greater interest rate risk entails closer supervisory scrutiny and potential capital surcharges in the short term, and lower expected profitability and capital accumulation in the medium to long term. We then proceed to dissect banks' credit allocation and find that banks with higher net duration reshuffled their loan portfolio away from long-term loans in an attempt to limit the increase in interest rate risk and targeted their lending contraction to small and micro firms. Firms exposed to banks with a larger exposure to interest rate risk were unable to fully rebalance their borrowing needs with other lenders, thus experiencing a relatively larger decrease in total borrowing during the monetary tightening episode.
Keywords: E51; E52; G21; 330; Interest rate risk; Duration gap; Bank lending channel; Financial Stability